UMP receives TERAJU RM2.27 million fund for IoT Innovation Fertigation Project - Rozana, Sahadan; Siti Nurfarmy, Ibrahim (2020)
Kuantan, 16 July 2020 - Universiti Malaysia Pahang (UMP) through the Centre of Industry and Community Network (ICoN) secured a grant worth RM2,270,000 from the Bumiputera Agenda Steering Unit (TERAJU) for the implementation of programmes under the Bumiputera Entrepreneur Development Fund (DPUB) 2020 in the East Coast Economic Region (ECER).